Linear dimensional changes and surface hardness of acetal resin in different periods of artificial saliva immersion in comparison with heat cure acrylic. - Sura S. Khalid; Widad A. AL-Nakkash (Erbil Dental Journal)
Background and Objectives: Acetal resins have a sufficiently high impact strength and resistance to organic solvents, the aim of this study was to evaluate the linear dimensional changes and surface hardness of acetal resin and compare it with heat cure denture base resin in different periods of artificial saliva immersion. Methods: Forty specimens were divided into two main groups according to the type of material used (heat cure resin and acetal resin). For each test 10 specimens were used. In this study two tests were performed. 10 maxillary denture bases for linear dimensional change by using digital microscope (Dino-lite Digital microscope) to measure the linear distance between reference points on the denture base. Measurements were per formed in four interval times first after processing, second after storage in the artificial saliva for 24 hours, third after storage in saliva for 15 days, and fourth after storage in saliva for 30 days. Also 10 specimens for Rockwell surface hardness test were prepared in this study. Results: For the linear dimensional change test, after processing T-test revealed a highly significant difference between acrylic and acetal groups in the AB line, a significant difference between the studied groups in the CD line, and a non-significant difference between the studied groups in BC, DA lines. While after immersion in saliva for 24 hrs., 15 days, 30 days: T- test revealed no significant difference between acrylic and acetal groups. The acetal group exhibited higher surface hardness mean value (92.90); while the acrylic group exhibited a lower mean value (74.53) Conclusion: Acetal resin can be used with limitation as an alternative to acrylic denture base in removable partial and complete dentures. Concerning linear dimensional change after processing: Nonsignificant difference between acrylic and acetal in BC, DA lines, statistically highly significant difference in AB line and significant difference in CD line. The immersion in saliva for three periods- 24hrs, 15 days, 30 days has no significant diffeence on linear dimensional change on both acrylic and acetal denture bases. Acetal group exhibited higher surface hardness than acrylic group.